Respecting privacy in care services. Issue 6 (28th November 2019) - Bates, Peter; McLoughlin, Brendan
Abstract : Purpose: In care homes concerns about abuse have established a culture where all information pertaining to a person must be shared, and little attention is paid to privacy in its broader sense. The purpose of this paper is to take a human rights perspective and consider how information governance may impact on the health, well-being and quality of life of residents. It proposes a proactive approach and presents a template for a privacy impact assessment which services could use to improve their approach to privacy, protecting the human rights of those in their care, contributing to their independence and improving outcomes. Design/methodology/approach: A review of historical and current thinking about the value of privacy in human services and wider society leads to a series of challenges to the way in which privacy is upheld in residential care services. Findings: Recent preoccupations with data privacy have led to a myopic neglect of broader considerations of privacy. Whilst it continues to be important to protect the confidentiality of personal data and to ensure that residents are protected from abuse, human services that provide 24 hour care in congregated settings must not neglect broader components of privacy. Research limitations/implications: Privacy impact assessments have been widely used to check whether data privacy is being upheld. The broader concept that might be termed "Big Privacy" is introduced within which data privacy is but one section. It is suggested that big privacy is severely compromised in residential care settings, thus denying residents their human right to privacy. The extent of such violation of rights should be investigated. Practical implications: Having set out the potential reach of the human right to privacy, important work needs to be done to find out how privacy might be upheld in the real world of congregate residential care. Some service providers may have solutions to the organisational challenges, have addressed staff training needs and revised risk assessment strategies so that privacy is upheld alongside other rights. Social implications: Nearly half a million people live in congregate residential care settings in England, and deprivation of privacy is argued to be a significant deprivation of human rights. Occasional tragedies and scandals in congregate settings create pressure for increasing the level of surveillance, and the right to privacy is sacrificed. This paper offers a challenge to this process, arguing that competing rights need to be balanced and privacy is an essential component of a decent quality of life. Originality/value: Personal growth and development depends to some extent on choice and control over access to privacy. Recent changes in the law regarding data protection have narrowed our thinking about privacy until it is a small concept, largely concerned with data handling. This paper invites consideration of big privacy, and invites congregate residential care settings to consider how a deep and broad definition of privacy could transform these services.